Precios y crisis en una economía rioplatense. Santa Fe (1790-1850) - Carina Frid (América Latina en la Historia Económica, 2017)
This study examines price evolution in Santa Fe district (Rio de la Plata) since the late years of colonial domination (when Santa Fe’s prices converged with regional prices) to mid-nineteenth century. Monastic sources provided information of prices of commodities (cattle, hides, wheat) as well as prices of consumption goods (sugar, tobacco, yerba mate, wine, aguardiente, salt, grease, tallow, canvas). Long-term prices and price indexes offer new evidence both of inflationary cycles as well as economic breakdown from 1815 to 1850.